Mid-term results of Scarf osteotomy in hallux valgus - Fuhrmann, Renée A. (Springer-Verlag, 2010)
We performed a retrospective study on 178 Scarf osteotomies with a mean follow-up of 44.9 months (range 15–83 months). Clinical rating was based on the forefoot score of the American Orthopaedic Foot and Ankle Society (AOFAS). Weight bearing X-rays were used to perform angular measurements and assess the first metatarsophalangeal joint (MTP 1). At follow-up the mean AOFAS score had improved significantly (p < 0.001), but only 55% of the feet showed a perfect realignment of the first ray. Patients with a hallux valgus angle exceeding 30° and pre-existing degenerative changes at the MTP 1 joint displayed inferior clinical results (p < 0.05). Nearly 20% of the patients suffered from pain at the MTP 1 joint. This was clearly attributed to an onset or worsening of distinct radiographic signs of arthritis (p < 0.05) resulting in painfully decreased joint motion. Comparing radiographic appearance three months postoperatively and at follow-up, we found that radiographic criteria (hallux valgus, first intermetatarsal angle, hallux valgus interphalangeus, MTP 1 joint congruency, arthritic lesions at MTP 1) worsened with time.